INFLUENCE ENTREPRENEURIAL LEARNING INTEREST ON STUDENT ENTREPRENEUR SMK BOJONEGORO - Sriatun Sriatun; Umi Kulsum; Andio S (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This study aims to determine the influence of entrepreneurial learning on students' interest in entrepreneurship smkn in the district of Bojonegoro. This research is a quantitative approach. The variables of this research is the study of entrepreneurship as an independent variable,interest in entrepreneurship as the dependent variable. This study is a population with a class XII student respondents, amounting to 182 students. Data collection techniques using questionnaires and documentation. These results indicate that the positive effect on entrepreneurial learning entrepreneurship interest of 39.6%.Keywords: Teaching Entrepreneurship, Entrepreneurship Interests.